The Role of Planetary Health in the Context of Healthcare Sustainability; An Assessment of the Knowledge, Attitudes & Practices of Healthcare Sector Workers in Egypt - Abdelhafez, Marwa (AUC Knowledge Fountain, 2025)
Introduction: Climate change imposes escalating threats to human health and well-being globally. The healthcare sector, as a key contributor to environmental degradation, must address its ecological footprint while supporting climate change adaptation and mitigation policies that promote planetary health. This study investigates Egyptian healthcare professionals' awareness, attitudes, and practices regarding planetary health and healthcare sustainability and explores barriers to their implementation. With healthcare at the frontlines of climate change impacts, assessing professionals' readiness for this role, provides evidence to mobilize Egyptian health systems to safeguard community health within a climate-challenged future. This study addresses a critical knowledge gap and stimulates progress toward sustainable healthcare in Egypt. Methods: A cross-sectional study design used a standardized questionnaire to measure the knowledge, attitudes, and practices (KAP) of the healthcare sector personnel in Egypt. The collected data were analyzed using descriptive, correlation, and regression methods. Results: The findings highlight current gaps in the climate literacy of healthcare workers revealing moderate knowledge levels (52%) and a notable disparity between attitudes (77%) and sustainable practices (18%). The findings also provide a perspective on incorporating sustainability into healthcare delivery, as it recognizes the lack of time, awareness, and patient interest as the main barriers to implementing sustainable health practices in Egypt. Conclusion: This research provides baseline data on Egyptian healthcare practitioners' readiness to incorporate planetary health principles into their medical practice. The findings can inform educational policies and interventions to build the healthcare workforce's capacity for planetary health, enabling the sector to exemplify sustainability leadership and contribute to the global efforts in its war against climate change and advancing planetary health.